2006
DOI: 10.1124/mol.105.021782
|View full text |Cite
|
Sign up to set email alerts
|

2-Fluoro-3-(4-nitro-phenyl)deschloroepibatidine Is a Novel Potent Competitive Antagonist of Human Neuronal α4β2 nAChRs

Abstract: A patch-clamp technique in a whole-cell configuration was used to examine the functional activity of recently developed 2-fluoro-3-(substituted phenyl)deschloroepibatidine analogs on two major subtypes of neuronal nicotinic acetylcholine receptors (nAChRs), ␣4␤2 and ␣3␤4, that predominate in the central and peripheral nervous systems, respectively. These epibatidine analogs have been shown previously to possess high binding affinity to ␣4␤2 but not to ␣7 nAChRs and to inhibit nicotine-induced analgesia in beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
41
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(46 citation statements)
references
References 34 publications
5
41
0
Order By: Relevance
“…When tested in a nicotine discrimination assay in rats, RTI-7527-102 did not mimic the effects of nicotine (Tobey et al 2012). These effects in mice are consistent with in vitro data showing that RTI-7527-102 has low efficacy, as evidenced by electrophysiological responses at both human and rat α4β2 nAChR expressed in Xenopus oocytes (Abdrakhmanova et al 2006; Ondachi et al 2012). The efficacy of RTI-7527-36 and RTI-7527-76 at α4β2 nAChR in vitro has not been established.…”
Section: Introductionsupporting
confidence: 89%
“…When tested in a nicotine discrimination assay in rats, RTI-7527-102 did not mimic the effects of nicotine (Tobey et al 2012). These effects in mice are consistent with in vitro data showing that RTI-7527-102 has low efficacy, as evidenced by electrophysiological responses at both human and rat α4β2 nAChR expressed in Xenopus oocytes (Abdrakhmanova et al 2006; Ondachi et al 2012). The efficacy of RTI-7527-36 and RTI-7527-76 at α4β2 nAChR in vitro has not been established.…”
Section: Introductionsupporting
confidence: 89%
“…[119] This trend of affinity/selectivity is confirmed by the work of other researchers [120] who have reported that compounds 58 show selectivity for the b2-containing receptors in binding studies; interestingly, the 4-CN derivative 58 b (X = H, Y = CN) possesses some agonistic properties on rat a3b4 nAChR (measurement of 86 …”
Section: Rbsupporting
confidence: 71%
“…The data in Table 1 indicate that the binding free energies calculated for the favorable binding of antagonists (1-20) with the closed-channel receptor and for the favorable binding of agonists (21)(22)(23)(24)(25)(26)(27) with the open-channel receptor are all close to the corresponding experimentally derived binding free energies. The good agreement between the computational and experimental data suggests that the determined binding structures and calculated binding free energies are reasonable.…”
Section: Resultsmentioning
confidence: 65%
“…As seen in Table 1, the ∆G bind value calculated for each of the antagonists (1-20) binding with the closed-channel R4 2 receptor is much lower than that calculated for its binding with the open-channel receptor. In contrast, the ∆G bind value calculated for each of the agonists (21)(22)(23)(24)(25)(26)(27) binding with the open-channel R4 2 receptor is much lower than that calculated for its binding with the closed-channel receptor. The calculated relative binding free energies are qualitatively consistent with the aforementioned notion concerning the modeled binding structures, i.e., all of the antagonists bind more favorably with the closed-channel receptor, whereas all of the agonists bind more favorably with the open-channel receptor.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation